Disparities in management and outcomes of myocardial infarction in multiple sclerosis: A matched cohort study. (October 2020) - Marrie, Ruth Ann; Tremlett, Helen; Kingwell, Elaine; Schaffer, Stephen Allan; Yogendran, Marina; Zhu, Feng; Fransoo, Randy; Garland, Allan
Background: Although multiple sclerosis (MS) confers an elevated risk of acute myocardial infarction (AMI), little is known about how it influences management of AMI. Methods: Using population-based administrative (health) data from two Canadian provinces, we conducted a retrospective matched cohort study. We identified people with MS who had an incident AMI, and up to five AMI controls without MS matched on age, sex, and region. We compared the likelihood of undergoing cardiac catheterization within 30 days of AMI, time to revascularization, use of recommended pharmacotherapy post-AMI, and mortality at 30 and 365 days post-AMI using multivariable regression models adjusting for potential confounders. We pooled findings across provinces using meta-analysis. Results: We identified 559 MS cases and 2523 matched controls. In the matched cohort, the MS cohort was less likely to undergo cardiac catheterization within 30 days of admission (odds ratio (OR) = 0.61; 95% confidence interval (CI) = 0.49–0.77), revascularization (hazard ratio (HR) = 0.78; 95% CI = 0.69–0.88), or to fill a prescription for recommended therapy. Mortality risk was higher in the MS cohort than in the matched cohort at 30 and 365 days post-AMI. Conclusion: Rates of diagnostic and therapeutic care, and survival after AMI were lower in the MS population than in a matched population.